2003
DOI: 10.1590/s0041-87812003000600002
|View full text |Cite
|
Sign up to set email alerts
|

Peri-intraventricular hemorrhage in newborns weighing less than 1500 grams: comparative analysis between 2 institutions

Abstract: PURPOSE:This study aims to characterize the peri-intraventricular hemorrhages in the neonatal period in very low birth weight newborns in 2 institutions that provide neonatal tertiary assistance.METHOD: This was a comparative and observational study in 2 neonatal intensive care units, the Maternity Hospital of Campinas and the "Centro de Atenção Integrada à Saúde da Mulher" of the State University of Campinas, from December 01, 1998 to November 30, 1999. We examined 187 newborns for peri-intraventricular hemor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 7 publications
0
5
0
1
Order By: Relevance
“…Em estudo em que se empregou US transfontanela para screening, os RNs com menos do que 32 semanas representaram quase metade da amostra, assim como nesse estudo em que a maioria da amostra teve menos que 30 semanas de gestação 8 . Outros estudos também registraram associação estatisticamente significativa entre idade gestacional menor do que 30 semanas e a ocorrência de HIC 19,20 . Apesar de não verificada diferença entre casos e controles, 71 (62,8%) RNs avaliados neste estudo apresentavam idade gestacional ≤ 30 semanas.…”
Section: Discussionunclassified
“…Em estudo em que se empregou US transfontanela para screening, os RNs com menos do que 32 semanas representaram quase metade da amostra, assim como nesse estudo em que a maioria da amostra teve menos que 30 semanas de gestação 8 . Outros estudos também registraram associação estatisticamente significativa entre idade gestacional menor do que 30 semanas e a ocorrência de HIC 19,20 . Apesar de não verificada diferença entre casos e controles, 71 (62,8%) RNs avaliados neste estudo apresentavam idade gestacional ≤ 30 semanas.…”
Section: Discussionunclassified
“…(19) Effects of time on PMV on the tracheobronchial secretion were proven by a study where through cytopathologic evaluation of the tracheal aspirate of 108 children under PMV, it was observed that in the first 4 days of PMV destroyed cells of the bronchial epithelium were found and a large amount of preserved and intact cells. However, in children ventilated for 4 and 10 days, some small clusters of preserved bronchial cells were seen, many deteriorated, also leukocytes, monocytes and macrophages, (18) showing occurrence of an intense inflammatory process associated to greater production of pulmonary secretion.…”
Section: Discussionmentioning
confidence: 98%
“…The artificial airway and PMV favor production and drying of secretion, causing airway obstruction and loss of the mucocilliary function. (3,17,18) Furthermore, children of the PMV≥5 group had been exposed for more days, to sedation (a therapy often used in neonates under PMV), that reduced the coughing reflex and elimination of secretion, leading to clinical conditions that course with pulmonary infection. (19) Effects of time on PMV on the tracheobronchial secretion were proven by a study where through cytopathologic evaluation of the tracheal aspirate of 108 children under PMV, it was observed that in the first 4 days of PMV destroyed cells of the bronchial epithelium were found and a large amount of preserved and intact cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations